2012
DOI: 10.1371/journal.pone.0033245
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Ocular Cells and Tissues by Atmospheric-Pressure Cold Plasma

Abstract: Background Low temperature plasmas have been proposed in medicine as agents for tissue disinfection and have received increasing attention due to the frequency of bacterial resistance to antibiotics. This study explored whether atmospheric-pressure cold plasma (APCP) generated by a new portable device that ionizes a flow of helium gas can inactivate ocular pathogens without causing significant tissue damage. Methodology/Principal Findings We tested the APCP effects on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 45 publications
8
114
0
6
Order By: Relevance
“…The amount of reactive species generated, including ozone, has been correlated with inactivation efficacy (12,36,(39)(40)(41). Among the reactive species generated during HVACP treatment, ROS contributed as major antimicrobial factors.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of reactive species generated, including ozone, has been correlated with inactivation efficacy (12,36,(39)(40)(41). Among the reactive species generated during HVACP treatment, ROS contributed as major antimicrobial factors.…”
Section: Discussionmentioning
confidence: 99%
“…Cold or nonthermal plasma has been actively deployed for practical purposes [7], and nonequilibrium atmospheric pressure plasma (NEAPP) therapy is currently hoped to fulfill new roles in the field of medical science [8][9][10]. In recent years, several therapeutic trials have been completed in the fields of tissue sterilization, blood coagulation, wound-healing promotion, and dental bleaching [11][12][13]. Additionally, it has been reported that plasma can exert antiproliferative effects on various cancer cell lines, possibly through induction of apoptosis [6,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that certain plasma species survive in water sufficiently long enough to constitute an alternative way of achieving disinfection through contact with the plasma-treated water (47). In a completely different departure from the potential that CAPs possess for the disinfection of contact lenses, it was recently demonstrated that the application of CAP to the surface of the eye is able to bring about the rapid disinfection of bacteria and fungi from the ocular surface without causing damage to the corneal epithelium and stroma (48).…”
Section: Discussionmentioning
confidence: 99%